IDENTIFIKASI SIFAT MAGNETIK TANAH DI DAERAH TANAH LONGSOR - Rahma Andini Pratiwi; Agum Gumelar Prakoso; Riski Darmasetiawan; Eleonora Agustine; Kartika Hajar Kirana; Dini Fitriani (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
A research has been conducted to identified magnetic properties of soil in landslides area. Soil samples had taken in two areas, area A located in landslides area and area B has not experienced landslides. We have identify magnetic parameter based on magnetic susceptibility measurements in 0,46 kHz  and 4,6 kHz . The measurement results showed that the  value of area A is 345.2 × 10-8 m3/kg to 571 × 10-8 m3/kg and the value of  in area B is 332.3 × 10-8 m3/kg to 668.1 × 10-8 m3/kg. The range of magnetic susceptibility values show that the magnetic minerals contained in the samples are classified as ferrimagnetic minerals. Relative difference between  and  is known as frequency dependent susceptibility . Calculated value of  in area A is about 2.65% to 3.33% and area B is 0.97% to 2.58%. The value of  indicates that area A contained more much superparamagnetic grains than area B. Soils that contain much superparamagnetic grains will be finer and easy to absorb water. The addition of soil mass by water could cause the soil more susceptible to landslide if located in steep slope.Keywords: Landslides, magnetic susceptibility, superparamagnetic grain.